THE ROLE OF HOSPITAL MANAGEMENT IN PRODUCTIVITY, REVENUE, EFFICIENCY, AND EFFECTIVENESS OF JKN PATIENT SERVICES: A CASE STUDY OF A PRIVATE HOSPITAL (XYZ) IN INDONESIA, 2023–2024 - Mulyadi Muchtiar; Umi Narimawati; Bobi Kurniawan (Taksasila Edukasi Insani, 2026)
This study examines how the management of XYZ Private Hospital governs the productivity, efficiency, and revenue of health services delivered to patients covered by the National Health Insurance (JKN) scheme under the INA-CBGs' prospective payment system. A case study design with a mixed-methods approach was employed, combining quantitative data from INA-CBGs' claim reports and JKN revenue (inpatient and outpatient) for 2023–2024 with qualitative data from in-depth interviews, focus group discussions, and a review of managerial documents. The findings indicate a sharp increase in JKN patient volume across almost all CMG and CBG groups, both inpatient and outpatient, accompanied by substantial growth in hospital revenue, positioning JKN as the primary revenue source. However, the casemix is dominated by medical cases at severity level 1, resulting in a high–volume–low–yield performance pattern that relies heavily on volume expansion rather than higher revenue per case. The analysis further reveals a persistent gap between actual care costs and INA-CBGs tariffs, especially for chronic and catastrophic conditions, exacerbated by undercoding, incomplete clinical documentation, and pending or lost claims, resulting in significant revenue leakage. Managerial interventions such as clinical pathway implementation, adherence to the National Formulary, quality and cost control programs, and strategic purchasing have improved operational efficiency but have not yet been fully integrated into a casemix-based revenue strategy that aligns productivity and efficiency with optimized reimbursement. The study concludes that the financial sustainability of JKN-dependent private hospitals crucially depends on the quality of casemix and claims governance, the alignment of operational efficiency with INA-CBGs algorithms, and business model innovation that balances social commitments with economic viability.Keywords: National Health Insurance (JKN); INA-CBGs; hospital management; casemix (CBG, CMG, severity), productivity, cost efficiency, and hospital revenue.